The power of the treacherous interpreter: Multilingualism in Jacques Audiard’s Un prophète - King, Gemma (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Representations of multilingualism as power are steadily increasing in prevalence in the French cinema of the twenty-first century. In contemporary multilingual French cinema, language functions not only as a vessel of meaning, but as a socially loaded and complex tool which is far from neutral. In films such as Welcome (Lioret, 2009), Polisse (Maïwenn, 2011), London River (Bouchareb, 2010) and De battre mon coeur s’est arrêté (Audiard, 2005), characters often exploit their multilingualism in order to exercise authority. Consequently, language can constitute a narrative device in itself, and a weapon to be harnessed and deployed in the pursuit of power. This article examines Jacques Audiard’s Un Prophète (2009), a film which contains dialogue in languages other than French and whose characters consistently employ code switching as a strategy for exerting dominance over one another. Significantly, the protagonist Malik’s multilingual power play comes to a head in his adoption of the role of what we shall label the treacherous interpreter, exploiting the measure of trust ritually assigned to the translator in order to manipulate his adversaries and wrest himself a unique position of power. The film thus calls into question not only the shifting status of marginalised languages in French society, but also the delicate and crucial role of translation in a social landscape marked by linguistic hybridity and intercultural conflict.